Characterization of RBP9 and RBP10, two developmentally regulated RNA-binding proteins in Trypanosoma brucei. Issue 4 (5th April 2017) - De Pablos, Luis Miguel; Kelly, Steve; de Freitas Nascimento, Janaina; Sunter, Jack; Carrington, Mark
Abstract : Abstract : The fate of an mRNA is determined by its interaction with proteins and small RNAs within dynamic complexes called ribonucleoprotein complexes (mRNPs). In Trypanosoma brucei and related kinetoplastids, responses to internal and external signals are mainly mediated by post-transcriptional processes. Here, we used proximity-dependent biotin identification (BioID) combined with RNA-seq to investigate the changes resulting from ectopic expression of RBP10 and RBP9, two developmentally regulated RNA-binding proteins (RBPs). Both RBPs have reduced expression in insect procyclic forms (PCFs) compared with bloodstream forms (BSFs). Upon overexpression in PCFs, both proteins were recruited to cytoplasmic foci, co-localizing with the processing body marker SCD6. Further, both RBPs altered the transcriptome from a PCF- to a BSF-like pattern. Notably, upon expression of BirA*-RBP9 and BirA*-RBP10, BioID yielded more than 200 high confidence protein interactors (more than 10-fold enriched); 45 (RBP9) and 31 (RBP10) were directly related to mRNA metabolism. This study validates the use of BioID for investigating mRNP components but also illustrates the complexity of mRNP function.